Le congé menstruel : entre avancée sociale et biais discriminatoire - Maéva Caron-Thérage (Criminocorpus)
Menstrual leave is a divisive issue. Whether it's a stigmatising measure, a discriminatory bias, a social advance or a measure to restore professional equality, opinions on this measure oscillate between vice and virtue. It is all the more divisive because it covers different realities. Linguistic precision is essential if this measure is to be a real social advance in the interests of professional equality. The term “menstrual leave” should therefore be replaced by the term “adaptation of the presence, working hours or working conditions of menstruating women due to the constraints associated with menstruation”. There is a risk of discrimination, but this should not obscure the need to address the issue of menstruation-related constraints in the workplace. Raising awareness of this issue and breaking the taboo surrounding menstruation, and women's bodies in general, would make it possible to go beyond the issue of gender equality and work towards a right for human beings by human beings.